Nonmonotonic particle-size-dependence of magnetoelectric coupling in strained nanosized particles of BiFeO3 - Sudipta Goswami (Nature Portfolio, 2018)
Abstract Using high resolution powder x-ray and neutron diffraction experiments, we determined the off-centered displacement of the ions within a unit cell and magnetoelectric coupling in nanoscale BiFeO3 (≈20–200 nm). We found that both the off-centered displacement of the ions and magnetoelectric coupling exhibit nonmonotonic variation with particle size. They increase as the particle size reduces from bulk and reach maximum around 30 nm. With further decrease in particle size, they decrease precipitously. The magnetoelectric coupling is determined by the anomaly in off-centering of ions around the magnetic transition temperature (T N ). The ions, in fact, exhibit large anomalous displacement around the T N which is analyzed using group theoretical approach. It underlies the nonmonotonic particle-size-dependence of off-centre displacement of ions and magnetoelectric coupling. The nonmonotonic variation of magnetoelectric coupling with particle size is further verified by direct electrical measurement of remanent ferroelectric hysteresis loops at room temperature under zero and ∼20 kOe magnetic field. Competition between enhanced lattice strain and compressive pressure appears to be causing the nonmonotonic particle-size-dependence of off-centre displacement while coupling between piezo and magnetostriction leads to nonmonotonicity in the variation of magnetoelectric coupling.